FGFC1 Selectively Inhibits Erlotinib-Resistant Non-Small Cell Lung Cancer via Elevation of ROS Mediated by the EGFR/PI3K/Akt/mTOR Pathway - Yan, Shike; Zhang, Bing; Feng, Jingwen; Wu, Haigang; Duan, Namin; Zhu, Yamin; Zhao, Yueliang; Shen, Shuang; Zhang, Kai; Wu, Wenhui; Liu, Ning (Frontiers in Pharmacology, 2022)
Non-small cell lung cancer (NSCLC) is one of the most common malignancies in the world. Epidermal growth factor receptor tyrosine kinase inhibitors (EGFR-TKIs) have been used as a first-line treatment for patients harboring with EGFR mutations in advanced NSCLC. Nevertheless, the drug resistance after continuous and long-term chemotherapies considerably limits its clinical efficacy. Therefore, it is of great importance to develop new chemotherapeutic agents and treatment strategies to conquer the drug resistance. FGFC1 (Fungi fibrinolytic compound 1), a type of bisindole alkaloid from a metabolite of the rare marine fungi Starchbotrys longispora. FG216, has exhibited excellent fibrinolytic and anti-inflammatory activity. However, the potent efficacy of FGFC1 in human cancer therapy requires further study. Herein, we demonstrated that FGFC1 selectively suppressed the growth of NSCLC cells with EGFR mutation. Mechanistically, FGFC1 treatment significantly induced the apoptosis of erlotinib-resistant NSCLC cells H1975 in a dose-dependent manner, which was proved to be mediated by mitochondrial dysfunction and elevated accumulation of intracellular reactive oxygen species (ROS). Scavenging ROS not only alleviated FGFC1-induced apoptosis but also relieved the decrease of phospho-Akt. We further confirmed that FGFC1 significantly decreased the phosphorylation of protein EGFR, phosphatidylinositol 3-kinase (PI3K), protein kinase B (Akt), and mammalian target of rapamycin (mTOR) in H1975 cells. Notably, PI3K inhibitor (LY294002) could promote the accumulation of ROS and the expression levels of apoptosis-related proteins induced by FGFC1. Molecular dynamics simulations indicated that FGFC1 can inhibit EGFR and its downstream PI3K/Akt/mTOR pathway through directly binding to EGFR, which displayed a much higher binding affinity to EGFRT790M/L858R than EGFRWT. Additionally, FGFC1 treatment also inhibited the migration and invasion of H1975 cells. Finally, FGFC1 effectively inhibited tumor growth in the nude mice xenograft model of NSCLC. Taken together, our results indicate that FGFC1 may be a potential candidate for erlotinib-resistant NSCLC therapy.